Investigate effect of neutron energy source for BNCT and digesting applications (Kurdistan University of Medical Sciences, 2016)
Introduction and Aim: the interaction of neutrons with light elements is used in neutron activation (NAA), neutron therapy (BNCT) and etc. in order to use the neutrons optimally, their energy spectrum has to be tailored to their practical purposes. When doing neutron therapy, the light elements which are located in the treatment site are activated and the instantaneous gamma ray has a specific value for each element using which the quantity of the lement is measured in the site. In this study, the effect of energy spectrum on the activation of neutron which is used in neutron therapy was studied. Material and method: MCNP softwere was used to simulate. First, all if the neutron spectra, such as neutron generator (MeV14) and the spectrum of the reactor and isotope sources were evaluated. The resulted spectrums of these sources were simulated by MCNP software. Considering the ability of this software in the transport of nwutrons and ogher particles and gamma flux measurements derived from them, the most optimal neutron energy spectrum of gamma for identifying htdrogen, carbon, and oxyeen elements was introduced. Findings:  the best spectrum of energy in order to identify the light elements in the energy range of BNCT (KeV10-1) is a spectrum of energy which has thermal neutrons (similar to Maxwell spectrum).Hydrogen has a good cross section for interaction with thermal neutrons. Oxygen and carbon has a good cross section with swift neutrons. By using neutron source MeV14 the neutron generator, hydrogen energe peak is less than when the source energy spectrum is similar to Maxwell and has higher oxyen and carbon peak. Conclusion:  Therfore, there is better output for therapeutic purposes, detection and analysis of light lelments like Maxwell (reactor or isotope sources). However, if the ratio of oxygen to carbon is measured and the mono energy sourse MeV14 be used, there is a better output.